Diversity and distribution of entomopathogenic nematodes (Steinernematidae and Heterorhabditidae) and their pathogenicity against Odoiporus longicollis in Mizoram, India - HRANG CHAL LALRAMNGHAKI; LALRAMLIANA LALRAMLIANA; VANLALHLIMPUIA VANLALHLIMPUIA; HMINGTHANZUALA HMINGTHANZUALA; MARY LALRAMCHUANI; VANRAMLIANA VANRAMLIANA; HMAR TLAWMTE LALREMSANGA; SA THING LALZARZOVI (Society for Indonesian Biodiversity, 2025)
Abstract. Lalramnghaki HC, Lalramliana, Vanlalhlimpuia, Hmingthanzuala, Lalramchuani M, Vanramliana, Lalremsanga HT, Lalzarzovi ST. 2025. Diversity and distribution of entomopathogenic nematodes (Steinernematidae and Heterorhabditidae) and their pathogenicity against Odoiporus longicollis in Mizoram, India. Biodiversitas 26: 5371-5384. Odoiporus longicollis, (Coleoptera: Curculionidae), commonly known as the banana pseudostem weevil (BPW), is a significant pest that reduces banana yield. Entomopathogenic nematodes (EPNs), recognized for their robust biocontrol ability, can control economically important insect pests and can be integrated into Integrated Pest Management (IPM) strategies. To identify EPNs, a survey was conducted across Mizoram, Northeastern India. Of all the 538 soil samples collected, 19 (3.53%) were positive for EPNs, representing13 of 36 collection sites (36.11%). The ITS and 28 rDNA sequence analyses identified 13 EPN isolates: seven Heterorhabditis indica, one H. baujardi, three Steinernema sangi, and two S. surkhetense. Pathogenicity tests were performed by exposing O. longicollis larvae to various concentrations of nematodes in Petri dish assay. Each EPN isolate was tested twice, with eight replicas per concentration (IJs/larva). BPW larval mortality ranged from 25-100% for both H. indica and S. sangi, 18.75-100 and 12.5-100% for H. baujardi and S. surkhetense, respectively. Based on LC50 and LT50 values, H. indica was the most lethal, followed by S. sangi, H. baujardi, and S. surkhetense. All EPN isolates successfully colonized dead larvae, with heterorhabditids multiplying more effectively than steinernematids. H. indica showed the highest multiplication rates, producing 77.5±14.44 x 103 and 125.97±31.49 x 103 IJs emerging at 10 and 200 IJs/insect, respectively. Nevertheless, the nematode multiplication rates, measured by the number of offspring produced, varied significantly among species [F (3, 28) = 67.57, p?0.05]. These findings on EPNs distribution enhance the knowledge on their geographical diversity and support their potential use in field management.